Comparative Analysis Of Polysemy And Homonymy In English - Nazarova, Navbahor Ahrorovna; Gaybullayeva, Ferangiz (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The study analyzes the semantic nature of polysemy, mechanisms of meaning development, and the role of metaphorical and contextual changes in expanding word meanings. It also investigates the types and formation of English homonyms from phonetic, historical, and morphological perspectives. The comparative analysis reveals the similarities and differences between polysemy and homonymy and highlights their functional role in communication and language economy. The research shows that both phenomena enrich the English lexical system and increase expressive possibilities in speech.